Understanding the role of social capital in enhancing community resilience to natural disasters: a case study of Muzarabani District, Zimbabwe - Kasimba, Rosemary (Rhodes University, Faculty of Humanities, Department of Sociology, 2018)
The central focus of the study was to seek an understanding of the role that Social Capital plays in enhancing the resilience and adaptive capacity of the community to floods and droughts in Muzarabani District of Northern Zimbabwe. The study was conducted in two of the wards in Muzarabani District namely Chadereka and Kapembere. In addition, the study sought to understand the coping and adaptation strategies employed by the most vulnerable groups such as the elderly, child heads, women and single heads of households. The specific objectives of the study were: to understand the effects of floods and droughts on residents' livelihoods and food security, examine residents' perceptions on droughts andfloods and to document community-based strategies utilised by women, child-headed families and the elderly to improve their livelihood and food security in the face of floods and droughts, explore different types of Social Capital that exist in the study area especially with regard to household resilience to disasters, comprehend the basis of residents' resilience to floods and droughts and the extent to which vulnerable groups rely on Social Capital when coping with these disasters and to examine the repercussions of residents' strategies on the community's institutional structures. The study was informed by Social Capital theory and the social network analysis. Social Capital plays a pivotal role in enhancing the resilience of the community to floods and droughts. Different types of Social Capital that exist and help people to deal with floods and droughts include linking, bonding, and bridging and victim Social Capital. Inhabitants within and outside villages support each other. Non-Governmental Organisations (NGOs) and the government are also working hand in hand with community members to reduce the negative impacts of floods and droughts. Volunteerism, generalised reciprocity and mutual understanding are also at the centre of interventions. The study employed both quantitative and qualitative approaches to achieve its objectives. Questionnaires, focus groups discussions, observations, transect walks, key informant interviews and some participatory methods were used to collect data. SPSS, content and thematic analysis were used to analyse data. The study found that floods and droughts negatively impact on human security, causing acute food shortages, intensifying poverty, spread of water related diseases, increasing divorce rates, children dropping out of school, reduced livestock and crop production, family disintegration, chaos in religion, exacerbating local unemployment as well as negatively affecting the wellbeing of community members. On a positive note, floods in Chadereka cause the deposition of alluvial soils that are good for crop production. However, in Kapembere, volunteerism is not very common; inhabitants are not yet trained about the concept. Community members have also formed cooperatives where they would give each other money or grain. In Chadereka, women have formed a mother-support-group to assist children with food in schools. Strategies being employed by the most vulnerable groups include casual labour, joining cooperatives, migration, taking children from school, hiring out cattle, selling of assets, riverine farming, growing drought-resistant crops, making use of indigenous knowledge systems, skipping meals and exploiting natural resources among others. Some women have resorted to prostitution to increase their resilience to floods and drought impacts such as poverty and acute food shortages. The elderly also hire out their cattle. They also rely on support from the government and NGOs. There are a number of challenges faced by residents in dealing with floods and droughts. Community social relationships, migration, casual labour and the sale of assets are the basis of the people's resilience against the impacts of floods and droughts. The study identified the following issues which all stakeholders involved could take note of: the government should not always be suspicious of disaster-risk reduction strategies implemented by NGOs as this scares away some of them that are willing to offer untied or unconditional assistance; timely and impartial distribution of agricultural inputs to inhabitants would be extremely useful. Moreover, the government needs to provide resources that support local organisations (formed by the local people) to assist the most vulnerable people in communities. Community leaders, together with the government and NGOs, are encouraged to hold awareness campaign programmes that dispel tribal and ethnic stereotypes, to promote local Social Capital among members of the community. Further investigations in the following areas are critical: A more comprehensive assessment of the determinants of resilience to droughts and floods in Zimbabwe is necessary.A study on the challenges faced by the disabled people and women in polygamous marriages and how they are adapting to floods and droughts, needs to be conducted and a critical investigation on the Zimbabwean government's strengths and weaknesses in enhancing the resilience of the community to floods and droughts is necessary among others.
Keywords: Social capital (Sociology) -- Zimbabwe; Natural disasters -- Zimbabwe -- Social aspects; Resilience (Personality trait) -- Zimbabwe; Food security -- Climatic factors -- Zimbabwe; Social sciences -- Network analysis; Cooperativeness -- Zimbabwe